Fetal macrosomia in pregnant women with gestational diabetes - Šegregur, Jadranko (Array, 2009)
Abstract: The aim of the study was to determine the frequency of fetal macrosomia in newborns from mothers with gestational diabetes mellitus (GDM) and healthy mothers, as well as determining the influence of fetal growth on pregnancy termination, on complications in pregnancy, during delivery and puerperium and on neonatal complications. In the study were included 351 pregnant women with GDM, as well as control group of 1502 healthy pregnant women. Newborns of mothers with GDM had significantly higher birth weight and length, ponderal index >2.85 was more frequent, they were macrosomic and hypertrophic (disproportional and proportional), had smaller Apgar score and more frequent neonatal complications (p<0.05). Fetal macrosomia and fetal hypertrophy alone or, particularly, connected with disproportional fetal growth, but disproportional hypotrophy as well, had significantly influence on greater frequency of delivery and puerperal complications, delivery completion with Cesarean section and neonatal complications in pregnant women with GDM